Invasive pneumococcal infections in children following transplantation in the pneumococcal conjugate vaccine era. Issue 1 (28th December 2016) - Olarte, Liset; Lin, Philana Ling; Barson, William J.; Romero, Jose R.; Tan, Tina Q.; Givner, Laurence B.; Hoffman, Jill A.; Bradley, John S.; Hultén, Kristina G.; Mason, Edward O.; Kaplan, Sheldon L.
Abstract: Background: Pediatric recipients of hematopoietic stem cell and solid organ transplants are at increased risk of invasive pneumococcal infections (IPI). Data on IPI in this population are scarce. To our knowledge, this is the first study describing the epidemiology of IPI among pediatric transplant recipients in the pneumococcal conjugate vaccine (PCV) era. Methods: We identified transplant recipients with IPI at 8 children's hospitals in the U.S. from our surveillance database (2000‐2014). Pneumococcal isolates were collected prospectively. Serotyping and antibiotic susceptibility were performed in a central laboratory. Categorical variables were analyzed by Fisher's exact test and continuous variables with nonparametric tests. Indirect cohort study design was used to calculate vaccine effectiveness. Results: We identified 65 episodes of IPI in transplant recipients. Recurrent IPI was observed in 10% of transplant recipients. The IPI crude incidence rate in solid organ transplant recipients was higher than in the general population. Most IPI episodes occurred >6 months after transplantation. Bacteremia and pneumonia were the most common presentations. Meningitis was unusual. No case fatalities were observed. Serotype 19A was the most common serotype (n=10), followed by 6C (n=7). In 2010‐2014, 37% of IPI was caused by PCV13 serotypes. Four cases of vaccine breakthrough were identified. Most isolates were susceptible to penicillin and ceftriaxone. Pneumococcal conjugate and polysaccharide immunization rates were low. Conclusion: Pediatric transplant recipients remain at increased risk of IPI in the vaccine era. Most cases presented as a late post‐transplant infection. The interval between transplantation and IPI may allow adequate time for pneumococcal immunization.